2021
DOI: 10.2169/internalmedicine.5820-20
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Blastic Plasmacytoid Dendritic Cell Neoplasm Following Sepsis by <i>Serratia marcescens</i>: A Case Report and Literature Review

Abstract: Spontaneous regression is rare in patients with blastic plasmacytoid dendritic cell neoplasm (BPDCN). An 85-year-old man presented with pancytopenia and skin lesions, and the bone marrow exhibited 79.6% CD4+, CD56+, CD123+, and TCL-1+ abnormal cells, with a normal karyotype; he was thus diagnosed with BPDCN. While being followed without chemotherapy, he was admitted due to sepsis induced by Serratia marcescens, which was successfully treated with antibiotics. Notably, his blood cell counts improved, and the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…(3) patients usually achieve at least partial remission in the skin, but similar bone marrow responses are unusual [16,[21][22][23][24]. Here, we present a case of SR of BPDCN, probably one of the few cases related to tissue infection.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…(3) patients usually achieve at least partial remission in the skin, but similar bone marrow responses are unusual [16,[21][22][23][24]. Here, we present a case of SR of BPDCN, probably one of the few cases related to tissue infection.…”
Section: Discussionmentioning
confidence: 85%
“…To date, there have only been five documented cases of spontaneous remission in BPDCN [16]. Here, we report one of the few cases described in the literature with a spontaneous complete remission of BPDCN, followed by relapse of the same disease within a short period of time.…”
Section: Introductionmentioning
confidence: 83%
“…CT has been mainly used to assess the extent and depth of the skin lesions, as well as the metastases in patients with BPDCN [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] . CT shows round and ovoid homogeneous cutaneous mass with soft tissue density with or without subcutaneous invasion as seen in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been at least eleven reports of BPDCN with CT findings, knowledge of chronological changes of CT findings has been limited. To our knowledge, only two case reports demonstrated the sequential CTs, both of which showed the chronological changes of the involved spleen [ 13 , 14 ], we first report the time course of skin lesions of BPDCN with sequential CT examinations [7] . CT demonstrated that multiple skin nodules fused to each other, resulting in a thickening of the entire skin, with some surface erosions and crusting in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation